Surgical Treatment of a Spontaneous Rupture of a Giant Common Carotid Artery Aneurysm: A case report - Hiller, Heinz Georg (CES Medicina, 2016)
Primary atherosclerotic aneurysms of the carotid artery are extremely are. Most cases are due to atherosclerotic disease, pseudoaneurysms secondary to neck trauma or previous surgery and mycotic aneurysms. Vascular surgeons will very likely encounter only 2 or 3 of these aneurysms in their professional life as surgeons. Although rare, these aneurysms pose a significant risk to the patient, due to embolisation of the thrombus, neurological complications, compression of adjacent neck structures and, more rarely, rupture from infection and previous surgery. The following case report describes the presentation and surgical treatment of a spontaneously ruptured gigantic common carotid artery aneurysm. DOI: http://dx.doi.org/10.21615/cesmedicina.30.1.8